Geotechnical Frontiers 2025 - Geotechnics of Natural Hazards - Beauregard Melissa S; Budge Aaron S (American Society of Civil Engineers (ASCE), 2025)
Selected papers from Geotechnical Frontiers 2025, held in Louisville, Kentucky, March 2-5, 2025. Sponsored by the Geosynthetic Materials Association, Advanced Textiles Association, and the Geo-Institute of ASCE. This Geotechnical Special Publication contains 62 peer-reviewed papers on the geotechnics of natural hazards. Topics include: climate change; earthquake engineering and soil dynamics; geotechnics of soil erosion; hazard mitigation; and landslides. GSP 366 will be of interest to geotechnical engineers, researchers, contractors, and other geoprofessionals working with climate change and natural hazards.